2020
DOI: 10.1002/cptc.201900269
|View full text |Cite
|
Sign up to set email alerts
|

Switching Photomechanical Response by a Structural Phase Transition in a Naphthalene Diimide Derivative

Abstract: A newly prepared photoresponsive material, specifically a naphthalene diimide molecule containing alkylamino groups, was found to exhibit a structural phase transition in the crystalline state. The phase transition dramatically altered the molecular arrangement from orthogonal π‐π stacking to parallel π‐π stacking. The photomechanical response of each crystal was also changed before and after the phase transition. While the as‐prepared crystal immediately responded to light irradiation (λ=370 nm), the responsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Smaller or thinner crystals often deform more easily than larger ones, especially for the photoresponsive crystals. [64,[216][217][218] The strain accumulated before phase change is more easily released in small crystals, and the occurrence of phase change is more difficult in higher density crystals with tightly packed crystal lattices. [218,219] Naumov and co-workers studied the relationship between the type of mechanical effect and crystal morphological scales (crystal length, width, thickness, and volume) during their phase transition.…”
Section: Dimensionality Of Scsc Phase Transition In Energy Conversion...mentioning
confidence: 99%
See 1 more Smart Citation
“…Smaller or thinner crystals often deform more easily than larger ones, especially for the photoresponsive crystals. [64,[216][217][218] The strain accumulated before phase change is more easily released in small crystals, and the occurrence of phase change is more difficult in higher density crystals with tightly packed crystal lattices. [218,219] Naumov and co-workers studied the relationship between the type of mechanical effect and crystal morphological scales (crystal length, width, thickness, and volume) during their phase transition.…”
Section: Dimensionality Of Scsc Phase Transition In Energy Conversion...mentioning
confidence: 99%
“…[216] Likewise, Goto et al found that the repeatability of the bending motion was related to crystal thickness in naphthalene diimide derivative crystals. [217] The switching photomechanical responsive crystal tends to bend if its thickness is less than 30 µm, whereas a thicker crystal do not show any bending. Apparently, reducing the size of crystal is beneficial for phase transition and motion.…”
Section: Dimensionality Of Scsc Phase Transition In Energy Conversion...mentioning
confidence: 99%
“…Naphthalene diimide (NDI) is an attractive acceptor block for building low bandgap and n-type conjugated polymers because of its excellent electron-withdrawing ability and charge transport properties. 27 Thus, NDI-based materials have been widely used in several applications, including chemical sensors, 28 molecular switching devices, 29 photovoltaic devices, 30 and catalysts. 31 However, the potential for using NDIbearing organic small molecules as photocatalysts for CO 2 reduction remains unexplored.…”
Section: ■ Introductionmentioning
confidence: 99%